1276. Assessment of Anti-biofilm Activity of Staphylococcus aureus Bacteriophages Against Clinical Isolates from Patients with Left Ventricular Assist Device Infections. (4th December 2021) - Ramirez-Sanchez, Claudia; Attai, Hedieh; Van Tyne, Daria; Shields, Ryan K; Yerushalmy, Ortal; Hazan, Ronen; Nir-Paz, Ran; Pride, David; Aslam, Saima
Abstract: Background: Staphylococcus aureus is a common cause of biofilm-mediated left ventricular device (LVAD) infections which are difficult to resolve with antibiotics alone and are associated with substantial morbidity and mortality. Recently, bacteriophages (phage) therapy has been used to resolve LVAD infections in a few cases. Our goal was to assess in vitro susceptibility and anti-biofilm activity of two S. aureus bacteriophages against clinical isolates from patients with S. aureus LVAD infections in order to develop a S. aureus phage cocktail for clinical use. Methods: Two bacteriophages, OMS1 and OMS2, from the Israeli Phage Bank, were assessed for lytic activity against 15 S.aureus isolates (9 methicillin resistant, MRSA and 6 methicillin susceptible, MSSA) via agar overlay method and plaque forming units (PFU)/mL were enumerated. We then formed bacterial biofilms after overnight incubation at 120 rpm in a 96-well plates in duplicate; experiments were repeated thrice. Wells were then treated with tryptic soy broth (TSB, control) or TSB containing phage at 109 PFU/mL for 24 hours. After washing, biofilms were stained with crystal violet and biomass quantified via optical density at 570mm. Results: All bacterial isolates were susceptible to both phages via agar overlay to varying degrees as determined by phage titers obtained via serial dilutions (Figure 1a, 1b). OMS1 led to significant reduction in biofilm of 7/9 MRSA and 3/6 MSSA isolates and OMS2 reduced biofilms in 9/9 MRSA and 4/6 MSSA isolates (Figure 1c). Phage titers and Biofilm Biomass Figure 1a) Phage titers in PFU/ml obtained from each bacterial isolate via agar overlay method. 1b) Representative agar plate demonstrating lytic plaques from OMS1 and OMS2 on a Staphylococcus aureus LVAD isolate. 1c) Biofilm biomass of Staphylococcus aureus isolates alone (SA) or with individual phage (SA+OMSA1 and SA=OMS2) assessed by optical density readings at 570 nm; error bars represent standard error of the mean. Conclusion: We demonstrated in vitro lytic and anti-biofilm activity of 2 S. aureus phages against clinical S. aureus isolates from patients with LVAD infection. Our data suggests that phage susceptibility measured with agar overlay does not always correlate with phage susceptibility of S. aureus biofilms, suggesting that more than one method should be used to assess in vitro activity. We plan to assess for synergistic activity with the phage combination. Disclosures: Ryan K. Shields, PharmD, MS, Shionogi (Consultant, Research Grant or Support) Ran Nir-Paz, MD, BiomX (Consultant)Technophage (Scientific Research Study Investigator, Advisor or Review Panel member) Saima Aslam, MD, MS, BioMx (Consultant)Cystic Fibrosis Foundation (Grant/Research Support)Gilead (Consultant)Johnson and Johnson (Consultant)Merck (Consultant)